Adding Expert Contributions to the Spatiotemporal Modelling of Avalanche Activity Under Different Climatic Influences. Issue 4 (3rd February 2015) - Lavigne, A.; Eckert, N.; Bel, L.; Parent, E.
Summary: We address the question of introducing expert knowledge in a hierarchical Bayesian spatiotemporal model. Specifically, we combine avalanche count data and an expert prior judgement about avalanche climatology to cluster French Alpine townships into two coherent groups. A spatial regression defines the a priori probability of belonging to each group and an innovative method is proposed to elicit its parameters by working with an expert on replicates of simulated maps. As a benefit of the extra data knowledge, we show the existence of robust north–south clusters of decreasing–increasing avalanche activity resulting from the interaction of local climate change patterns with altitude distribution. Spatial dependence of avalanche activity has also been inferred and is characterized by an anisotropy, with longer dependence along the north-west–south-east axis.